Ethnopharmacy Study of Medicinal Plants Lampung Tribe in Pekon Tabuan Island, District Cukuh Balak, Tanggamus Regency, Lampung Province - Oktoba, Zulpakor; Adjeng, Andi Nafisah Tendri; Romulya, Ari Irawan (Jurnal Jamu Indonesia, 2024)
People in the Indonesian archipelago have long used medicinal plants as an alternative disease treatment. Tabuan Island is an area in Cukuh Balak District, Tanggamus Regency, Lampung Province, where most people are Lampung Peminggir /Pesisir tribe who still practice empirical medicine with local wisdom. Ethnopharmacy studies on Tabuan Island in the Lampung tribe have never been conducted and published. The study aimed to explore the knowledge of local communities regarding the types of medicinal plants for the search and development of new medicines. This research method includes area studies and descriptive studies in the form of ethnopharmacognosy-ethnopharmacology approaches in the Tabuan island community in 4 (four) villages or Pekon namely Pekon Sawang Balang, Pekon Suka Banjar, Pekon Kuta Kakhang, and Pekon Karang Buah used participatory observation methods and open interviews. The results showed that the Lampung Peminggir ethnic group on Tabuan Island still maintains ethnopharmaceutical traditions by utilizing plants used as medicine in 36 families of 76 species to treat diseases used singly or as a concoction accompanied by jampi. The most widely used plant families are Fabaceae, Zingiberaceae, Malvaceae, Meliaceae, and Poaceae. These medicinal plants in the Fabaceae family are most widely used to remedy mouth ulcers and skin problems such as tinea versicolor, ringworm, itching, acne, dandruff, diarrhea, and diabetes. Leaves are the most widely used plant parts, as much as 49.52%, and the least used plant parts are herbs, thallus, and fungi, while most of these plants are obtained in the garden. The most common way of processing medicinal plants is by stewing.